Behavior of voices in the business and economic language: a case of English-Arabic translation - Talafha, Duaa; Kasuma, Shaidatul; Moindji, Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2023)
The present paper delves into business and economic English and Arabic texts to describe the language and translator's norms and to justify these norms with regards of voices translation. The sample is collected manually from two e-portals where 20 texts were drawn from each website. It is found that translators use oblique translation methods to render passive constructions into Arabic in their endeavor to attain more idiomatic Arabic. Although translators are inclined to use the active voice more than the passive, this usage is mostly limited to dynamic verbs where English active stative verbs were modulated to passive Arabic beside the reduced adjectival phrases. The only gain of meaning or effect is achieved when the active English stative verbs became dynamic Arabic passives in order to give a stronger reporting of information. The findings contribute in characterizing the business and economic voice’ behavior in English and Arabic in an attempt to integrate the findings with the findings of other genres.